Aspek Hukum Perlindungan Konsumen Atas Pemasaran Produk Kosmetik Berbahaya Oleh Pelaku Usaha Setelah Memiliki Izin Edar dan Akibat yang Ditimbulkan(Studi Kasus Produk Madame Gie) - putri, wulan sulistiana; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Based on facts that occur in society, it is often found that consumer rights as stated in article 4 of Law Number 8 of 1999 concerning Consumer Protection are not realized as they should be, such as the discovery of hazardous ingredients in 3 Madame Gie cosmetic products. The purpose of this research is to find out why 3 Madame Gie products were declared dangerous after having a distribution permit since 2018 and to find out what the consequences were. This study uses a normative juridical approach with library research data collection techniques. Based on the research results, madame gie can be withdrawn after having a distribution permit because hazardous materials were found during post-market supervision by BPOM and the resulting consequences are legal consequences in the form of administrative sanctions and non-legal consequences in the form of social sanctions